Successful repeated uterine artery embolization in postpartum hemorrhage with disseminated intravascular coagulation: a case report and literature review - Shunya Sugai; Taro Nonaka; Kana Tamegai; Tatsuhiko Sato; Kazufumi Haino; Takayuki Enomoto; Koji Nishijima (BMC, 2021)
Abstract Background Postpartum hemorrhage (PPH) is a potentially fatal condition requiring urgent and appropriate intervention. Uterine artery embolization (UAE) has a high hemostatic capacity for PPH, but it may fail. Disseminated intravascular coagulation (DIC) has been reported as a risk factor associated with the failure of UAE. Case presentation A 37-year-old primigravida with dichorionic diamniotic twins and placenta previa underwent cesarean section. The blood loss during surgery was 4950 mL. Hemostasis was achieved using an intrauterine balloon tamponade device. However, she lost a further 2400 mL of blood 5 h after surgery. We embolized both uterine arteries using gelatin sponges and confirmed hemostasis. She was suffering from DIC and received ample blood transfusions. However, a further 1300 mL of blood was lost 18 h after surgery and we performed repeated UAE, with complete recanalization of the uterine arteries on both sides and re-embolization with gelatin sponges. Her DIC was treated successfully by blood transfusions at this time, and she showed no further bleeding after the repeated UAE. Conclusions DIC is a risk factor for the failure of UAE. Repeated UAE may be effective after sufficient improvement of the hematological status in patients with PPH and DIC.